THE EFFECTS OF COVID19 PANDEMIC UPON TOURISM: A SAMPLE FROM THE CITY OF KARS - Ethem Topçuoğlu; Erdoğan Kaygın (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi)
This study aims to determine the effects of Covid 19 upon tourism sector in Kars. The study benefited from three methods, the first of which involved analyzing the articles by scanning via Nvivo analysis program. Secondly, a semi-structured interview was conducted with ten employees. However, this number was seen inadequate; thus, the questionnaire was conducted with 387 people to compensate for this inadequacy. The data were analyzed through SPSS and AMOS, and examined Covid 19 effects upon tourism on the basis of demographical variables. The results revealed that dismissals from hotels and restaurants were common, the business experienced a serious loss of income, they needed support from the government to recollect and at least one year was required to turn back to conditions before. The results indicated that people had a negative attitude towards tourism activities, hesitated to travel and thought that they would not be able to find service quality, sincerity and hospitality as they had before. Moreover, the study helped us realize that, due to Covid 19, females were more worried when compared to males; the married ones were more anxious in comparison to single ones; and the elderly had more anxiety when compared to the young.